Basal levels of enzymatic biomarkers and energy reserves in Porcellionides pruinosus - Ferreira, NGC
In the last decades biomarkers have been widely used for the assessment of effects and/or exposure to environmental contaminants, but to our knowledge few data has been published for isopod species. Along with biomarkers the quantification of energy reserves has also been used to evaluate organisms' energetic budget. Enzymatic biomarkers can also be useful to understand chemicals/stress modes of action. The aim of this study was to obtain information on biomarker basal level activities and energy contents of the isopod Porcellionides pruinosus as little information is available. Results can then be used as foundations for other ecotoxicological or biomonitorization studies and also as control values for evaluating isopod status in laboratory cultures. The cholinesterase (ChE) type of the isopod P. pruinosus was characterized using three substrates (acetylthiocholine iodide, propionylthiocholine iodide, and S-butyrylthiocholine iodide) and three ChE inhibitors (eserine hemisulfate, tetraisopropyl pyrophosphoramide (iso-OMPA) and 1,5-bis(4-allyldimethyl-ammonimphenyl) pentan-3-one dibromide (BW284C51)]. The results showed that this organism has only one cholinesterase form, the acetylcholinesterase with a mean basal level of 113.6 +/- 4.7 U/mg protein. Other biomarkers related to oxidative stress or metabolism were assessed, showing activity ranges of 3.0 +/- 1.1 U/mg protein for lactate dehydrogenase (LDH), 6.1 +/- 1.1 U/mg protein for catalase (CAT), 2.7 +/- 1.1 U/mg protein for glutathione peroxidase (GPx), 34.6 +/- 4.7 nmol/mg ww for lipid peroxidation (LPO) and 137.8 +/- 7.1 U/mg protein for glutathione S-transferases (GST) (mean +/- st. error). The carbohydrates and protein contents were 12290.8 +/- 56.4 J/mg organism (org) and 22905 +/- 57.5 J/mg org, respectively (mean st. error). The mean lipid content was 503.1 +/- 12.7 J/mg org. Our results were compared to other previous works with isopod species but also with other species, showing high levels of inter and intraspecific variability. Even tough this study can contribute as foundations for other studies as ChE characterization, optimization of homogenization procedures and basal levels for biomarker activity and energy reserves were described. (C) 2010 Elsevier Ltd. All rights reserved.